Unveiling Hidden Meanings: A Semiotic Exploration of Central Java’s Islamic University Logos Through Peirce’s Lens - Fatin, Manar Abdurra'uf; Zulfah, Siti (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
In the modern era, logo perception has become crucial as logos serve as visual representations of an institution's identity and values. This research emphasizes the critical role of logo symbolism in shaping the identity and communication strategies of State Islamic Universities (UIN) in Central Java, Indonesia. Despite its significance, there is a notable research gap in the semiotic analysis of these logos, particularly concerning the integration of Islamic identity with local cultural heritage. This study aims to decode the implicit meanings in the logos of UINs in Central Java, examining how these symbols reflect both the universities’ Islamic values and their modern, inclusive identities. Employing a qualitative descriptive methodology with semiotic analysis based on Charles Peirce’s semiotics theory and also Cerrato’s color theory, data were collected through documentation techniques from online repositories. The analysis covered logos from UIN Walisongo, UIN Raden Mas Said, UIN Salatiga, UIN Prof. K.H. Saifuddin Zuhri, and UIN K.H. Abdurrahman Wahid. Findings reveal that each logo carries layered symbolic meanings, incorporating symbols that reflect Islamic values while harmonizing with local culture. Elements such as gunungan, flowers, and color schemes (green, white, yellow, orange, gold, and black) are prevalent, symbolizing a commitment to preserving cultural values and advancing progressive Islamic education. This study highlights the importance of understanding logo symbolism for reinforcing institutional identity and enhancing public perception, offering insights that could strengthen the global competitiveness and appeal of UINs.